Early and Delayed 99mTc-MDP SPECT/CT Findings in Rheumatoid Arthritis and Osteoarthritis. (November 2017) - Abdelhafez, Yasser G.; Hagge, Rosalie J.; Badawi, Ramsey D.; Raychaudhuri, Siba P.; Chaudhari, Abhijit J.
Abstract : Abstract: We report the case of a 74-year-old man with seropositive rheumatoid arthritis (RA) and radiographic osteoarthritis (OA) who underwent dual-phase high-resolution 99m Tc-MDP SPECT/CT. Early radiotracer enhancement was noted in 2 RA joints of the right hand, both presenting with a ring-like uptake pattern around the joint, consistent with synovitis. Insignificant early enhancement was noted at the first carpometacarpal joint, despite presentation of CT features of OA. The delayed-phase enhancement patterns were distinct, showing asymmetry in RA joints, but a symmetric, joint-centered pattern for the OA joint.